Molecular detection of Shiga toxin genes and pathogenicity of Escherichia coli O157: H7 isolated from salad samples in Erbil city-Iraq - Ismail Saleh, Shean; Jalal Mahmood , Lanja; Tahsin Kakayi , Safin; Hassan Sdiq , Kwestan (Diyala Journal of Medicine, 2022)
Background: Escherichia coli O157:H7 is one of foodborne pathogenic bacteria that causes serious infections in people around the world. Cattle are a barrage of E. coli O157:H7, fresh products contaminated with cattle feces are the common sources for the pathogen. E. coli O157:H7 has the ability to survive well in the environment. Two main virulence factor genes of E. coli O157 have been detected in this study, which are responsible to produce shiga toxin and increase the pathogenicity of this bacterium. Objective: To find out the rate of fresh food contamination by E. coli, and detect the genes responsible for shiga toxin production and increase the pathogenicity of E. coli among isolates from salad samples. Patients and Methods: Two hundred salad and vegetable samples were collected from different restaurants and small shops in Erbil city from April - September (2019). Samples were cultured on eosin methylene blue (EMB) agar plates; typical E. coli with a metallic shine appeared. Polymerase chain reaction technique was used for detecting (uidA, rfbo157 and stx1, stx2) genes. Results: Overall, 32% (64/200) of salad samples were contaminated by E. coli as identified by culturing on EMB agar. Then isolated E. coli was confirmed by detecting the presence of uidA gene and the rate was 88% (56/64). Pathogenicity and toxin production detection was done for all confirmed E. coli isolates, by detecting the presence of rfbo157 gene (479 bp), among 56 isolates only (4) isolates was positive for rfbo157 gene, and (7) isolates showed positive result for shiga toxin. Conclusion: This study focuses on the serotype E. coli O157:H7, a high percentage of E. coli was detected in salad samples which indicated the fecal contamination. The presence of rfbo157 gene and stx1, stx2 are the indications for pathogenicity and shiga toxin production respectively.